(3GdhGajI aj TQM GdcGajIs - (3MSf Hf eMeO Hf TQaTGg GdMSjfj GdCSJQGHGPj, Qcf GdOjf , J (B715 (3g` s; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj HYO Cf TQMJ cJGH GdcGajI aj GdfMh TQMJg KGfjkG ebJUQkG Ydi Md CdaGXg s
(3BNQgG (B:s
(3haj jGGeQCI GVQHf, GVQHj aj Gdhba, de jYde Cfg jOd Yf Gdfhf hGdeMPha GdeQOhO Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs